"As Tunisian I feel ashamed by this disgusting presenter": Collective face threat and identity positioning on Facebook. (August 2022) - Labben, Afef
Highlights: Investigates collective face threat on Facebook. Investigates acts of positioning following collective face threat. Provides a taxonomy of discursive strategies used to respond to collective face threat. Shows that Tunisian Facebookers positioned themselves in multiple ways following face threat. Shows that Tunisian Facebookers' perception of their and others' rights and duties resulted in different positioning moves. Shows that cultural values influence online face concerns and discursive practices. Abstract: In this paper, I draw on identity theories as developed within social psychology in general, and Positioning Theory in particular, to investigate the discursive strategies that Tunisian Facebookers use to counter collective face threat, and how they position themselves vis-à-vis in-group and out-group members. To categorize the strategies, a post-data collection taxonomy was developed, which allowed for the quantitative and qualitative analysis of the comments. Wherever appropriate, the analysis also considered the range of multimodal semiotic means the commentators used to communicate their emotional stances. Results show that Tunisian Facebook users positioned themselves in multiple ways following face threat, and that their perceptions of their and others' rights and duties resulted in various discursive positioning moves. Results also show that Tunisian Facebookers used linguistic as well as multimodal resources to convey their emotions. Previous intracultural findings about lexemic and interactional aspects of Tunisian face seem to be relevant for intercultural digital communication involving Tunisians as findings of this study illustrate the influence of cultural values on online face concerns and show the importance of considering the wider offline context when accounting for digital discursive practices.